(3GdJLGQI GdGdcJQhfjIs - (3ZGdH jGSjf(B, (3SYOs; (3GdYdGb(B, (3HTjQ YHGSs ((3YeGf(B:s (3OGQ GdefGgL dfTQ(B,s, 2004)
(3jMJhj GdcJGH Ydi ebOeI GdCSS GdfXQjI h GdJbfjI ddCYeGd GdEdcJQhfjI , JLGQI GdJLRFI GdEdcJQhfjI JcfhdhLjG GdCfJQfJ hGdJLGQI GdEdcJQhfjI , GdJLGQI GdEdcJQhfjI , ehGVjY eJbOeI aj Mbd GdJLGQI GdEdcJQhfjI, UjGZI hJfajP ESJQGJjLjI GdJLGQI GdEdcJQhfjI, eONd dJUeje ehGbY GdJLGQI GdEdcJQhfjI (B.s
(3HjHdjhZQGajG U(B.319-320s
Keywords: (3GdGfJQfJs; (3GdJLGQI (B- (3JcfhdhLjG GdeYdheGJ hGdGJUGds; (3GdJLGQI GdOhdjIs